WORLD EXPERIENCE OF SOCIAL PROTECTION OF THE POPULATION IN THE CONTEXT OF ECONOMIC CRISES - Zulaykho, Kodirova; Shakhnoza, Abdullaeva (The journal of contemporary issues in business and government, 2021)
The article looks at the concept of social protection of population in a state of crisis and the development of waysthe mechanism of social protection, which makes research topic relevant. The scientific article gives scientific definitions to such categories as "social protection","social policy" by various scholars and authors. In addition, the article groups social protection programs, summarizes and comprehensively, analyzes the theoretical and scientific approaches to improving their effectiveness. Having done an extensive analysis of the research materials, the author makes a conclusion about the urgency strengthening measures for social protection of the population in order to avoid furthereconomic recession.